A Quarter for the Theater and a Flower on the Vest in Order to Listen to the Concert: Grecia’s Society Entertainment in the First Half of the XX Century, Costa Rica - Vargas Trejos, Yendry (Revista de historia., 2020)
The aim of this article is to analyze the way how the community of Grecia (Costa Rica) spent their free time between the 1920s and the 1960s by means of enjoying music, dances, theater, and places of social gathering. The way how the conformation of a more urban social space facilitated the appropriation of leisure expressions and recreational habits similar to the ones practiced by the bourgeoisie in San José (the capital city) is explained in the article. The research is based on information gather from the Archivo Nacional of Costa Rica, Grecia’s Town Hall files, newspapers, interviews, and photos